Environmental Performance Companies and Sustainable Development: The Case Of Nestle El Jadida - A. Aajjane, O. El Gueddar, T.Aarab, A. Sahib Eddine, F. Rahmouni, (International Journal of Scientific Research and Management (IJSRM), 2014)
: Environmental performance of the enterprise is a central concept in management science. This notion is mobilized in the management literature to assess the implementation of recently announced by the company’s sustainable development strategies. The evaluation of environmental performance requires the implementation of tools to produce and provide information on the environmental impacts of and the measures taken to address the scarcity of natural resources. Among these tools, environmental indicators are increasingly used by companies as recommended by the ISO 14001 standards, they allow managers to assess the level of environmental performance of their business and identify potential areas for improvement. The research at the Nestle factory El Jadida demonstrates that the assessment of environmental performance based on environmental indicators allows, while respecting the environment, economic gain and social emergence in the context of new governance for sustainable development.